Emergence of nanotechnology in efficient fertilizer management in soil - Faizan, Mohammad; Karabulut, Fadime; Khan, Ira; Akhtar, Mohd. Sayeed; Alam, Pravej (Elsevier, 2024)
We cant't imagine human life without agriculture as it gives basic essentials for us to live a healthy life. In recent years, agricultural productivity is decreasing due to various anthrpogenic activities. World population increasing day-by-day and it is very challenging to complete the nutritional demands of the increasing popu-lation with novel technologies in the present scenario. As a promising contributor, nanotechnology having ability to alter agricultural efficiency by providing resistance against abiotic stresses, increasing nutrient absorption, controlling plant diseases, reduce the fertilizers, and fill the hole between food supply and demand. Nanotechnology is the branch of science dealing with the nanoparticles (NPs), nano-fertilizers, nano-capsule, and nano-sensors for effective agricultural services and decreasing harmful impact to the envi-ronment. Nanotechnology can be found to be very beneficial in the field of nano-fertilizers. Small particle size and large surface area of NPs increase the interaction with plant surface and uptake of plant nutrients. Vari-ous NPs can be used as fertilizer by contributing to many levels in agricultural applications with the superior properties of NPs. Therefore, the presented literature may help to cover-up the gap between agricultural pro-ductivity and demands. We thoroughly explained the recent advances of nanotechnology to supplement and fertilizers, potential effects of smart fertilizer on soil-plant system, and mechanism of nano-fertilizer uptake by plants. Thus, in this review, we have also explained the opportunities and challenges together with aims to uplift future studies towards promising applications of nano-fertilizers to increase nutritional value and yield.(c) 2023 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Agricultural productivity; Nano-fertilizer; Soil nutrients; Sustainable agriculture